Controlled breeding and reproductive management in water buffaloes (Bubalus bubalis) using Eazi Breed controlled internal drug release - Hiremath, Shivayogi (J S Afr Vet Assoc, 2015)
Buffalo reproduction is considerably affected by late maturity, poor oestrus symptoms and long postpartum periods. This study was undertaken to evaluate the efficiency of Eazi Breed controlled internal drug release (CIDR), an intravaginal progesterone-releasing device, in relation to oestrus and fertility. Five hundred true anoestrus buffalo cows, in the age group 4–6 years in 10 villages of Dharwad district in Karnataka state in India, were randomly selected and treated with CIDR for 9 days. Two mL of Cidirol (1 mg oestradiol benzoate) was administered intramuscularly to all animals on day 10. Forty-two buffaloes (8.4%) that failed to show oestrus signs (1.6%) or showed weak signs of oestrus (6.8%) after the first treatment were treated again 72 h after the Cidriol injection with a new device, and inseminated after the expression of oestrus. After the second treatment all the animals showed oestrus signs. The percentage of buffaloes showing intense oestrus was 67.40%, intermediate oestrus was shown by 25.80%, whilst 6.80% buffaloes showed weak oestrus even after the second treatment. The buffaloes showing oestrus signs were inseminated twice with an interval of 12 h, starting 12 h after the start of the oestrus signs. In 86 buffaloes showing prolonged oestrus signs a third insemination was done. The conception rates were 85.16%, 60.47% and 44.11% respectively in buffaloes showing intense, intermediate and weak oestrus. Transrectal palpation of the genital tract was performed 45–60 days post-insemination to diagnose pregnancy status, and in doubtful cases pregnancy was reconfirmed at 90 days after insemination. Out of 500 buffaloes treated in this way 380 animals became pregnant and the pregnancy rate was 76%. This study revealed the usefulness of Eazi Breed CIDR along with Cidirol treatment in buffaloes to improve their reproductive performance.